Design of refractory SiC/ZrSi2 composites: Wettability and spreading behavior of liquid Si-10Zr alloy in contact with SiC at high temperatures. Issue 4 (April 2020) - Giuranno, Donatella; Bruzda, Grzegorz; Polkowska, Adelajda; Nowak, Rafal; Polkowski, Wojciech; Kudyba, Artur; Sobczak, Natalia; Mocellin, Francesco; Novakovic, Rada
Abstract: Reactive infiltration of liquid Si-enriched alloys into C- or SiC-based preforms is a viable cost-less alternative to manufacture dense and highly performant SiC-based and MMC composites. In view to design and optimize liquid-assisted processes such as reactive infiltration, fundamental investigations on the interfacial phenomena occurring when the liquid Si-based alloys are in contact with C and SiC substrates, are crucial steps. In this context, targeted wettability studies may provide indications for predicting the key factors strongly influencing the reactive infiltration mechanisms, such as, unexpected interaction phenomena, etc. In particular, such preliminary experience may be helpful in finding the suitable set of operating conditions for fabricating tailored composites via reactive infiltration process. Aiming to "mimic'' the conventional industrial processes for manufacturing SiC/ZrSi2 refractory composites, the sessile drop method was applied to study the interfacial phenomena occurring at Si-10 % atZr/SiC interfaces over the temperature range of T =1360 °C-1450 °C.